Multiple-objective optimization in green fuel production via catalytic deoxygenation reaction with NiO-dolomite catalyst - Hafriz R.S.R.M.; Arifin N.A.; Salmiaton A.; Yunus R.; Taufiq-Yap Y.H.; Saifuddin N.M.; Shamsuddin A.H. (Elsevier Ltd, 2023)
Catalysts; Diesel engines; Multiobjective optimization; Oils and fats; Surface properties; Surface reactions; Catalytic deoxygenation; Deoxygenation reactions; Deoxygenations; Dolomite; Green fuel; Heterogeneous catalyst; Response-surface methodology; Waste cooking oil; ]+ catalyst; Nickel oxide